Changes in ventilation and perfusion following lower lobe endoscopic lung volume reduction (ELVR) with endobronchial valves in severe COPD. (15th May 2019) - Yang, Li; Hsu, Kelvin; Williamson, Jonathan P.; Peters, Matthew J.; Ho‐Shon, Kevin; Ing, Alvin J.
Abstract: Background: We have previously reported significant improvements in ventilation and perfusion (VQ) and V/Q matching in the contralateral lung, especially the non‐targeted lower zone in patients with severe COPD following upper lobe ELVR with endobronchial valves. However, V/Q changes after lower lobe ELVR have not been described. Methods: Seven patients with lower lobe heterogeneous emphysema underwent unilateral lower lobe ELVR at Macquarie University Hospital. Lung function tests, 6‐minute walk tests (6MWT), St George's Respiratory Questionnaire (SGRQ) and planar differential VQ scans were performed at baseline and at 1, 3 and 12 months post‐ELVR. Results: Compared to baseline, patients showed significant improvements in FEV1 (0.83 ± 0.09L‐0.97 ± 0.12L, p  < 0.05), 6MWD (200.33 ± 56.54 m‐274.24 ± 48.03 m, p  < 0.05) and SGRQ (61.13 ± 5.33‐42.86 ± 6.99, p  < 0.05) at 3 months after ELVR. This improvement was maintained at 12 months. There was a corresponding significant improvement in the differential ventilation (30.21 ± 3.04%‐37.82 ± 3.76%, p  < 0.05) and perfusion (31.77 ± 2.53%‐35.60 ± 2.58%, p  < 0.05) of the contralateral non‐targeted upper zone. Conclusions: Within the limitations of a small sample size, we have found that in heterogeneous severe COPD patients undergoing ELVR targeting the lower lobes, there are clinical and PFT improvements similar to that reported in ELVR targeting upper lobes. Contralateral improvement in V/Q matching also occurs following lower lobe ELVR with the greatest improvement in the contralateral upper zone, suggesting the contralateral upper lobe should be the least affected lobe if the lower lobe is targeted in ELVR. These findings need to be confirmed in a study with a larger number of patients.